The efficacy of Tuina for asthma: A protocol for a systematic review and meta-analysis - Wang, Changhong (Medicine (Baltimore), 2020)
BACKGROUND: Asthma is one of the most common chronic diseases in the world, with ∼100 million asthma patients worldwide. China has become one of the countries with the highest asthma death rate in the world. Asthma is a chronic airway inflammatory disease. Patients with this disease may have symptoms such as cough, wheezing, and difficulty breathing. For many years, Western medicine has mainly used anti-inflammatory, anti-bronchial spasm, asthma, cough, and oxygen to treat this disease, but the effect is not good. Tuina is a common treatment for asthma in China. But at present, there is no systematic evaluation report on its therapeutic effectiveness and safety. This protocol aims to reveal the efficacy and safety of Tuina for treating asthma. METHODS: The following databases will be searched by electronic methods: PubMed, EBASE, WHO International Clinical Trials Registry Platform, Embase, the Chinese Biomedical Literature Database (CBM), Wan-fang Data (WANFANG), the China National Knowledge Infrastructure (CNKI), and other sources from inception to November 2020. Bias risk, subgroup analysis, data synthesis, and meta-analyses will be assessed with RevMan V.5.3 software if the data is met inclusion conditions. RESULTS: This study will present a quality evidence of Tuina for the treatment of astma patients. CONCLUSION: The systematic review will present reliable evidence to judge whether or not Tuina is a safe and effective intervention for asthma patients. International Platform of Registered Systematic Review and Meta-Analysis Protocols (INPLASY) registration number: INPLASY2020110100.